Implementasi Model Pembelajaran Kooperatif Tipe Teams Games Tournament untuk Meningkatkan Aktivitas dan Hasil Belajar Teknik Passing Bola Voli - Anak Agung Ngurah Putra Laksana; I Wayan Adnyana; I Gede Agus Adi Saputra; I Kadek Yudha Pranata; I Putu Eri Kresnayadi; Gede Hendri Ari Susila (Jurnal Pendidikan Kesehatan Rekreasi, 2021)
In the field, there are still many students who are not able to do well by combining playing volleyball from the initial attitude, the attitude regarding the ball and the final attitude. This study aims to improve the activities and learning outcomes of volleyball passing in class X1 SMA Negeri 4 Singaraja. This research includes classroom action research which was carried out in 3 cycles. The research subjects were 32 students of class X1 public senior high school number 4 Singaraja, consisting of 17 male students and 15 female students. The data in this study were analyzed using descriptive statistics with the results obtained in the first cycle, namely the average percentage of student learning activities classically ( ) 73,9% (active), while in cycle II ( ) 76,3% (very active) and in cycle III ( ) 77,4% (very active). While the level of completeness of learning outcomes in cycle I was 81,3% (good), in cycle II was 90.7% (very good) and in cycle III was 96.8% (very good). So from cycle I, cycle II and cycle III there was an increase and had met the completeness criteria of at least 75% classically and 65% individually. It can be concluded that the activities and learning outcomes of volleyball passing have increased through the implementation of the Teams Games Tournament (TGT) cooperative learning model in class X1 public senior high school number 4 Singaraja.